Two-Phase Lineage Specification of Telencephalon Progenitors Generated From Mouse Embryonic Stem Cells - Nasu, Makoto; Esumi, Shigeyuki; Hatakeyama, Jun; Tamamaki, Nobuaki; Shimamura, Kenji (Frontiers in Cell and Developmental Biology, 2021)
Proper brain development requires precisely controlled phases of stem cell proliferation, lineage specification, differentiation and migration. Lineage specification depends partly on concentration gradients of chemical cues called morphogens. However, the rostral brain (telencephalon) expands prominently during embryonic development, dynamically altering local morphogen concentrations, and telencephalic sub-regional properties develop with a time lag. Here, we investigated how progenitor specification occurs under these spatiotemporally changing conditions using a three-dimensional in vitro differentiation model. We verified critical contributions of three signalling factors for the lineage specification of sub-regional tissues in the telencephalon, ventralising sonic hedgehog (Shh) and dorsalising bone morphogenetic proteins and WNT proteins. We observed that a short-lasting signal is sufficient to induce sub-regional progenitors and that the timing of signal exposure for efficient induction is specific to each lineage. Furthermore, early and late progenitors possess different Shh signal response capacities. This study reveals a novel developmental mechanism for telencephalon patterning that relies on the interplay of dose- and time-dependent signalling, including a time lag for specification and a temporal shift in cellular Shh sensitivity. This delayed fate choice through two-phase specification allows tissues with marked size expansion, such as the telencephalon, to compensate for the changing dynamics of morphogen signals.